A Proposed Audit Program to Integrate Modern and Traditional Auditing Methods - Dr. Faez Abdulhasan Jasim Allami; Lect. Dr. Ali Khazaal Jabbar (Periodica Journal, 2022)
The study proposes an integrated audit program that balances the role of classic and new auditing methodologies. Within the legal framework controlling the audit profession and based on relevant norms and procedures, this program aims to enhance the audit process, decrease and identify mistakes and fraud in financial statements, and reduce audit risks. The benefits of these two types of methodologies may be used as a guide for the auditor when creating an audit strategy and program to meet the audit objectives.
Keywords: methodologies; guide; creating; program